2015
DOI: 10.1186/s12960-015-0048-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of quality and relevance of curricula development in health training institutions: a case study of Kenya

Abstract: The World Health Organization lists Kenya among African countries experiencing health workforce crisis catalysed through immigration, underproduction, inconsistent quality of production and unequal distribution. Strengthening health training institutions to increase production of high-quality health workers is acknowledged as a measure to mitigate the crisis.IntraHealth International’s USAID-funded FUNZOKenya Project (2012–2017) undertook an assessment to identify the bottlenecks to increasing the number and q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 4 publications
1
16
0
Order By: Relevance
“…From a broader perspective, the need for competent Nutrition and Dietetics professionals as highlighted in this study aligns with the aspirations by the Government of Uganda to train undergraduates with the necessary skills and abilities to meet Uganda's development needs [15,16]. Research undertaken in Kenya showed that undertaking curricula review is critical to improving the quality and relevance of health workforce training [47]. Although the possession of knowledge and skills required for health systems performance is key for all health professionals [20], whether undergraduates can possess all the expected/required competencies by the time they graduate is contested.…”
Section: Nutrition and Dietetic Services Requested And Provided To Comentioning
confidence: 75%
“…From a broader perspective, the need for competent Nutrition and Dietetics professionals as highlighted in this study aligns with the aspirations by the Government of Uganda to train undergraduates with the necessary skills and abilities to meet Uganda's development needs [15,16]. Research undertaken in Kenya showed that undertaking curricula review is critical to improving the quality and relevance of health workforce training [47]. Although the possession of knowledge and skills required for health systems performance is key for all health professionals [20], whether undergraduates can possess all the expected/required competencies by the time they graduate is contested.…”
Section: Nutrition and Dietetic Services Requested And Provided To Comentioning
confidence: 75%
“…Lecturers and tutors lacked modern EPI training.In-service training (Pre-service and in-service training tutors of health worker)Umar et al (2011) [24]Sokoto and Kebbi States, Nigeria• Tutors in all the five pre-service health training institutions in Sokoto and Kebbi states of Nigeria. (Training nurses, midwives, community health officers (CHO), community health extension workers (CHEW), senior community health worker (SCHEW) and junior community health worker).• Questionnaire on bio-data of health workers’ tutors, their highest educational qualification, years of service, in-service training received on EPI,• The five components of Reaching Every Ward (REW) namely planning and management of resources, establishing or reactivating fixed post and outreach services, supportive supervision and community linkage and monitoring for action.• Although in-service training demonstrated significant statistical association on overall knowledge of respondents’ (df = 1; F = 8.62; P < 0.0001), less than half of the respondents had received an in-service training on EPI after graduation.• There is a need for retraining of tutors on the current trends in immunization and management.Pre-service curriculumMumbo et al (2015) [25]Kenya• 14 institutions from 18 institutions identified for initial collaboration with the project towards strengthening health workforce training• The assessment collected data from 533 respondents.• The assessment questions relating to quality of curriculum sought responses on the following: availability of curriculum guidelines, curriculum responsiveness to institutional mission and regularity of curriculum review as well as involvement of stakeholders in the review process• The findings revealed major gaps in quality and adequacy of curricula in the training institutions.• A national standard framework to guide curricula review process is lacking• Curricula did not adequately prepare students for clinical placement, as most failed to directly respond to national health needs.In-service trainingWeeks et al (2000) [26]Kyrgyzstan, Central Asia• Medical workers (41 health facility staff).• Supervisors of health information records.• Duration of training: two days• Simplify DPT records and reports, collect only relevant reports and decentralized decision making.• Modify the existing data collection forms and records, developed graphs that could be constructed manually.• Analytic supervision checklist developed for the 3 levels of supervision.• HCW training and data management• 95% improved data collection and data reporting and quality.In-service training (Evaluation of dashboard)Poy et al (2017) [27]6 African countries: Angola, Chad, DR Congo, Ethiopia, Nigeria, South Sudan• Immunization programme managers• Creation and implementation of multidimensional monitoring tool (i.e. dashboard) designed• to provide information on immunization system performance• The capacity building workshop and job aids development facilitated the dashboard reporting process clarifying both indicator definitions and reporting timelines• Data availability and quality improved between the first quarter of 2014 and fourth quarter of 2015, especially for the process indicators.In-service trainingWard et al (2017) […”
Section: Resultsmentioning
confidence: 99%
“…However, it also demonstrates the forward thinking of the Aksum leaders in their ability to quickly adapt to the circumstances and to deliver successful modules in Dermatology and Ophthalmology. A study carried out in Kenya evaluating the quality and relevance of curriculum development in health training, found that there are major gaps in the quality and adequacy of the training [ 13 ]. The study also highlighted the need for a national standard framework to guide curriculum review.…”
Section: Discussionmentioning
confidence: 99%